2021
DOI: 10.1111/evo.14280
|View full text |Cite
|
Sign up to set email alerts
|

Selection favors adaptive plasticity in a long‐term reciprocal transplant experiment

Abstract: Spatial and temporal environmental variation can favor the evolution of adaptive phenotypic plasticity, such that genotypes alter their phenotypes in response to local conditions to maintain fitness across heterogeneous landscapes. When individuals show greater fitness in one habitat than another, asymmetric migration can restrict adaptation to the lower quality environment. In these cases, selection is predicted to favor traits that enhance fitness in the higher-quality (source) habitat at the expense of fitn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 106 publications
(287 reference statements)
2
10
0
Order By: Relevance
“…Theoretical work has suggested that plasticity reduces fitness when environmental stochasticity is high and unpredictable (Reed et al, 2010), and we propose that the dramatic effects of river management on P. ruthii habitat may have selected against plasticity in addition to the potential for plasticity to be maladaptive in response to novel conditions. We encourage future studies that evaluate the lifetime fitness consequences of phenotypic plasticity under realistic field conditions (Anderson et al, 2021;Baythavong et al, 2011;Baythavong & Stanton, 2010;Van Buskirk & Steiner, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical work has suggested that plasticity reduces fitness when environmental stochasticity is high and unpredictable (Reed et al, 2010), and we propose that the dramatic effects of river management on P. ruthii habitat may have selected against plasticity in addition to the potential for plasticity to be maladaptive in response to novel conditions. We encourage future studies that evaluate the lifetime fitness consequences of phenotypic plasticity under realistic field conditions (Anderson et al, 2021;Baythavong et al, 2011;Baythavong & Stanton, 2010;Van Buskirk & Steiner, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Plasticity also can be maladaptive, which is especially likely when it is elicited in response to environmental conditions that are novel, under which selection would not yet have occurred (Snell‐Rood et al, 2018). But research on the adaptive nature of phenotypic plasticity in plant traits has been limited (Wei et al, 2020; but see Anderson et al, 2021; Baythavong et al, 2011; Baythavong & Stanton, 2010). The relatively high plasticity of P. ruthii in response to altered light and water availability in our study was associated with reductions in photosynthetic rate (which generally correlates with growth; Kruger & Volin, 2006; Figures 1b and 3d), leaf production (as a measure of growth; Figure 3a), and flowering (Appendix 2: Figure S1) in the directions of future change that we anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated studies such as ours are essential for better understanding how spatial and temporal shifts in environmental factors alter selective pressures on quantitative trait divergence between species, including traits contributing to reproductive isolation. Repeated reciprocal transplant experiments have been instrumental in identifying local adaptation in both individual species [ 17 , 51 , 70 , 71 ] and hybrid zones [ 72 ], but ours is one of the few to identify how both spatial and temporal variation in selection contributes to or erodes species divergence. While divergence and speciation are often viewed as directional processes, especially in reference to self-fertilizing species that have lost much of the genetic variation that precedes differentiation [ 73 ], it is important to acknowledge the more nuanced and varying nature of species boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…While spatially and temporally varying selection have been studied extensively in the context of local adaptation and genetic variation within species [1,3] (review in [15][16][17]), it is less well known how spatially and temporally varying selection affects divergence and reproductive isolation between species. This is particularly important to understand when species occur sympatrically and are incompletely reproductively isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, model systems represent a limited diversity of form and function and cannot answer critical research questions that apply to a diversity of species with different life histories, geographic distributions, symbioses, or evolutionary histories (Goldstein and King, 2016). For example, the annual species A. thaliana would not be appropriate for investigating issues pertaining to perennial species, such as resource allocation to current vs. future reproduction under different environmental contexts (Williams, 1966; Bell, 1980; Obeso, 2002; Sletvold and Ågren, 2015) or the extent to which interannual temporal variation in conditions influences the evolution of adaptive plasticity in long‐lived species in which individuals can experience multiple years of heterogeneous conditions (Van Kleunen et al, 2007; Wagner and Mitchell‐Olds, 2018; Anderson et al, 2021). Furthermore, studies that exclusively occur in laboratory settings with traditional model systems lack the ecological relevance to inform our understanding of how multiple abiotic and biotic factors drive evolution in complex natural environments.…”
Section: Genus‐level Attributes Traits Of Primary Model Species Genus...mentioning
confidence: 99%